2010
DOI: 10.1021/ja910769j
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Convergent Entry to the Diazofluorene Antitumor Antibiotics: Enantioselective Synthesis of Kinamycin F

Abstract: We describe a 12-step enantioselective synthetic route to the complex anticancer antimicrobial agent kinamycin F (3). Key to the success of the route was the development of a three-step sequence for construction of the diazonapthoquinone (diazofluorene, blue in structure 3) function of the natural product. This sequence comprises fluoride-mediated coupling of a beta-(trimethylsilylmethyl)-cyclohexenone and halonapthoquinone, palladium-mediated cyclization to construct the tetracyclic scaffold of the natural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Most notably, the two halves of the lomaiviticins are united by a single carbon-carbon bond (red in 5 and 6). Within lomaiviticin B (6), the tertiary (C-3/C-3′) hydroxyl groups have undergone 1,2-addition to the adjacent ketone functions, to form a rigid bis(tetrahydrofuranol) structure. Additional significant differences include the presence of dihydroxynaphthoquinone residues in the lomaiviticins (as opposed to a juglone residue in the kinamycins) and 2-4 2,6-dideoxyglycosides, a-oleandrose, and b-N,N-dimethylpyrrolosamine, about the periphery of the lomaiviticins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, the two halves of the lomaiviticins are united by a single carbon-carbon bond (red in 5 and 6). Within lomaiviticin B (6), the tertiary (C-3/C-3′) hydroxyl groups have undergone 1,2-addition to the adjacent ketone functions, to form a rigid bis(tetrahydrofuranol) structure. Additional significant differences include the presence of dihydroxynaphthoquinone residues in the lomaiviticins (as opposed to a juglone residue in the kinamycins) and 2-4 2,6-dideoxyglycosides, a-oleandrose, and b-N,N-dimethylpyrrolosamine, about the periphery of the lomaiviticins.…”
mentioning
confidence: 99%
“…Structures of kinamycins A (1), C (2), and F (3), lomaiviticin aglycon (4), and lomaiviticins A (5) and B(6).…”
mentioning
confidence: 99%
“…Our synthesis started with meta -cresol ( 12 ) which was protected as a TIPS ether and then subjected to Birch reduction conditions to afford cyclohexa-1,4-diene 13 [9]. Enantioselective Sharpless dihydroxylation proceeded in good chemoselectivity but with modest yield and optical purity (25% ee).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 9 in turn could be traced back to silyl enol ether 10 . Ent - 10 was first reported by Herzon and co-workers [9] and is derived from phenol silyl ether 11 via Birch reduction and dihydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…[ xxxix ] After extensive studies into conditions for oxidative dimerization (>1500 experiments), they found that treatment of the TMS enol ether 71 with Mn(III) hexafluoroacteoacetate produced 26% yield of the desired 1,4-diketone 72 , along with 12% of the undesired isomer possessing the bis-epimeric stereochemistry across the linking σ-bond. Use of the exo -mesityl acetal proved crucial in obtaining a facial preference for 72 .…”
Section: Natural Product Synthesismentioning
confidence: 99%